The living house an anthropology of architecture in South-East Asia - Waterson, Roxana (Oxford University Press, 1991)
This work presents a detailed description of the centrally significant role of houses in South-East Asian social systems. Focusing on Indonesia, the book traces the historical links between architectural forms, revealing a much wider field of enquiry, closely related to the distribution of Austronesian languages and cultures, and extending as far as Madagascar, Japan, and Oceania. A vivid picture of how people shape buildings and buildings shape people, this study provides new insights into kinship systems, gender symbolism, cosmological ideas, and life itself.